THE IMAGINARY OF FAMILIES OF SCHOOLCHILDREN ON EVERYDAY HEALTH PROMOTION - Nabarro, Marta; Nitschke, Rosane Gonçalves; Tafner, Daniela Priscila Oliveira do Vale (My University, 2020)
ABSTRACT Objective: to understand the imaginary of families on health promotion, as well as its limits and strengths in the family routine. Method: a qualitative research of the descriptive-exploratory type. It was conducted with 12 families whose children attend a Municipal preschool and elementary educational center. Data collection was conducted between October and November 2018 by means of individual semi-structured interviews. The material was organized by coding the information until reaching the sense nucleus of the text, thus discovering the classes and their connections. Data analysis involved processes of preliminary analysis, ordering, key connections, coding, and categorization. Results; three subcategories emerged: The imaginary of fathers and mothers about health promotion in the family routine; Strengths that can contribute to the promotion of health in the family routine; and Limits of the families to promote health in the family routine. Conclusion: from the perspective of the imaginary, the importance of this research strengthens the possibility of sustaining strategies which favor an improvement in the everyday life of these families, further reinforcing community health to attain a healthy lifestyle.
Keywords: health promotion; family; children; child obesity; everyday activities; nursing; disease prevention; family nursing